Short‐Term Repeatability of Magnetic Resonance Elastography at 3.0T: Effects of Motion‐Encoding Gradient Direction, Slice Position, and Meal Ingestion. Issue 3 (2nd September 2015) - Zhang, Jiming; Arena, Claudio; Pednekar, Amol; Lambert, Brenda; Dees, Debra; Lee, Vei Vei; Muthupillai, Raja
Abstract : Purpose: Magnetic resonance elastography (MRE) can estimate liver stiffness (LS) noninvasively. We prospectively assessed whether motion‐encoding gradient (MEG) direction, slice position, or high‐caloric food intake affects the repeatability of MRE measurements of LS. Materials and Methods: Twenty healthy volunteers (8 women, 12 men; age, 48 ± 12 years) were imaged in a 3.0T scanner at four timepoints: twice after overnight fasting (B1, B2 ) and twice after consuming a 1050‐calorie standardized meal (A1, A2 ; after 30 and 60 min, respectively). Each session comprised sequential MRE acquisitions in which MEG was applied in three orthogonal directions with three slices positioned over the liver for each. Between sessions, the participants were repositioned to assess test–retest reproducibility. Results: The LS measurements before/after food intake were 3.36 ± 1.31 kPa/3.22 ± 1.03 kPa, 2.04 ± 0.33 kPa/2.27 ± 0.38 kPa, and 2.47 ± 0.50 kPa/2.64 ± 0.76 kPa for MEG superimposed along the anterior–posterior (AP), foot–head (FH), and right–left (RL) directions, respectively. Before and after food intake, LS estimates were lower and more reproducible (<10% coefficient of variation) when the MEG was in the FH direction, not the AP or RL direction. Liver stiffness estimates were significantly elevated after meal consumption when the MEG was in the FH direction ( P < 0.05 for B1 vs. A1, B1 vs. A2, B2 vs. A1, and B2 vs. A2 ). Conclusion: MRE estimates of LS were highly reproducible, particularly when MEG was applied in the FH direction, suggesting that this method could be used for long‐term monitoring of antifibrotic therapy without repeated biopsies. High‐caloric food intake resulted in slightly elevated LS on MRE. J. MAGN. RESON. IMAGING 2016;43:704–712.